2017
DOI: 10.1093/brain/awx056
|View full text |Cite|
|
Sign up to set email alerts
|

Glycation potentiates α-synuclein-associated neurodegeneration in synucleinopathies

Abstract: α-Synuclein misfolding and aggregation is a hallmark in Parkinson's disease and in several other neurodegenerative diseases known as synucleinopathies. The toxic properties of α-synuclein are conserved from yeast to man, but the precise underpinnings of the cellular pathologies associated are still elusive, complicating the development of effective therapeutic strategies. Combining molecular genetics with target-based approaches, we established that glycation, an unavoidable age-associated post-translational m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
148
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(169 citation statements)
references
References 91 publications
8
148
0
Order By: Relevance
“…A recent study has shown that glycation of α-synuclein, a protein whose aggregation is the hallmark of PD, enhanced the aggregation and reduced clearance of toxic oligomers. In vitro and in vivo studies using flies and mice showed that enhanced glycation is toxic while glycation inhibitors reduce aggregation and enhance clearance of α-synuclein, and rescue behavioral phenotypes (Vicente Miranda et al, 2017). Furthermore, these studies also explain the significantly increased risk of PD amongst diabetics.…”
Section: Modeling the Influence Of Ages In Neurodegenerative Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has shown that glycation of α-synuclein, a protein whose aggregation is the hallmark of PD, enhanced the aggregation and reduced clearance of toxic oligomers. In vitro and in vivo studies using flies and mice showed that enhanced glycation is toxic while glycation inhibitors reduce aggregation and enhance clearance of α-synuclein, and rescue behavioral phenotypes (Vicente Miranda et al, 2017). Furthermore, these studies also explain the significantly increased risk of PD amongst diabetics.…”
Section: Modeling the Influence Of Ages In Neurodegenerative Diseasesmentioning
confidence: 99%
“…The key finding in the study was that glycation enhanced the aggregation and inhibited clearance of HTT suggesting a direct role of protein glycation in neurodegeneration (Vicente Miranda et al, 2016). In a recent study utilizing flies and mice, it was also shown that accumulation of toxic oligomers due to age-related glycation of α-synuclein resulted in disruption of synaptic transmission in the neurons (Vicente Miranda et al, 2017). …”
Section: Using Invertebrate Models To Study the Impact Of Agesmentioning
confidence: 99%
“…2628 Reactive endogenous small molecules and environmental toxins are known to promote covalent α-synuclein crosslinking, and their potential to nucleate and/or stabilize toxic oligomeric species has sparked recent efforts to define their roles in PD. 2, 14, 2931 …”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in PD, aggregates of the protein α‐synuclein (αS) are found in Lewy bodies3 within neuronal cells. These proteins are often heavily post‐translationally modified, for example, αS undergoes phosphorylation, nitration and truncation,4, 5, 6 this makes it important to be able to characterise the real endogenous aggregates formed in cells, as these can differ from those formed by unmodified proteins.…”
mentioning
confidence: 99%